Gut microbiota dysbiosis and the role of its person-to-person transmission in the development of non-communicable diseases - Chaves-Jiménez, Gloriana (2024)
The gut microbiota plays an integral role in carrying out digestion processes as well as having profound health implications. Environmental factors such as the type of diet an individual consumes dictate its composition and its impact on the host. The disruption of the gut microbiome causes dysbiosis. Some presently considered non-communicable diseases are related to gut dysbiotic microbiota. In recent years, there has been increasing interest in studying gut microbiota’s person-to-person transmission and its role in health associated effects. In this review, an insight is provided into these topics; additionally, a proposition is made to further study the effects of factors such as cohabitation and personal diet on transmission rate speed.